Primary hepatic Ewing sarcoma: a very infrequent case report - Ozturk Ates; Fatma Bugdaycı Basel; Nazan Bozdogan; Bulent Aksel; Omur Berna Oksuzoglu (Italian Journal of Medicine, 2015)
Ewing sarcoma (ES) is a member of small round cell tumors of which contains Wilms’ tumor, neuroblastoma, rhabdomyosarcoma and lymphoblastic lymphoma. ES occurs most commonly in the bone but infrequently occurs in the soft tissues without involvement of the bones. Primary involvement of the liver is even rarer. We report the case of 24-year-old female patient with abdominal pain. Abdominal computed tomography scan showed hepatic large cystic lesion. Liver biopsy showed tumoral cells with small narrow stoplasmic and hyper chromatic nucleus evaluated as small round cell tumor. Immunohistochemical study of the lesion revealed CD99 and bcl-2 positive, cytokeratin, LCA, CD138, chromogranin, synaptophysin, myoD1, terminal deoxynucleotidyl transferase and myoglobin negative the diagnosis primary hepatic ES. A research for any other tumor involvement by using positron emission tomography yielded only hepatic involvement revealed. The patient treated with vincristine-cyclophosphamide- adriamycin and ifosfamide-etoposide alternately chemotherapy then hepatic tumor regressed. Patient operated on hepatic wedge resection. She has continued on chemotherapy and she has been doing well at the sixth month of diagnosis.